The Challenges of Online Learning during the COVID-19 Pandemic: An Essay Analysis of Performing Arts Education Students - Roy Martin Simamora (Studies in Learning and Teaching, 2020)
COVID-19 pandemic has changed the way of learning in higher education. Teaching, and learning activities that are usually carried out with face-to-face meetings have turned into virtual meetings in various online learning applications. This paper aims to analyze student essays in the form of perspectives or responses about the challenges of online learning during the COVID-19 pandemic. This paper collected fifteen students as samples in the Fundamentals of Education I course who were actively involved in online learning activities. Online learning provides various instructions led by the lecturer. Instructions can be synchronous (communication where participants interact in the same time space as video conferencing, zoom, google meet, and WebEx) or asynchronous (time-separated communication such as e-mail, google form, streaming video content, posting lecture notes and social media platforms). This study used a qualitative approach. The researcher then collecting, reading and highlights each student's response that is considered relevant for analysis. This paper has shown so many responses about the challenges experienced by the students while studying online, such as, positive and negative impact of online learning, economic conditions, anxiety during online learning, government should think and planned, the risk of user data security, face-to-face class to online learning, ability, finding effective online learning media and expectations.